Assessing the Impact of Fiscal Policy on Economic Growth Rates - I. A. Sokolov; E. O. Matveev (Мир новой экономики)
Relevance. The Guidelines for Budget, Tax and Customs Tariff Policy for 2024 and for the planning period 2025–2026 show that there will be a significant increase in expenditures for all funds of the Russian budget system. The expenses’ structure is changing significantly: it is expected to shift towards power expenses against the backdrop of a slight reduction in investments in human capital, social policy and the national economy growth. To ensure the budgetary balance required by law, the state predicted an increase in the tax burden in the next three years. This paper attempts to assess the impact of these changes on GDP dynamics. The authors calculated multipliers, including in key functional sections of the budget classification, to assess changes in fiscal policy, tax, and budget expenditure. Methods. We based these calculations on the impulse responses of the structural VAR model of the Russian economy. Also, the authors assessed the model on data for 2004–2021 to reckon the average-sized model (10 indicators) involved having used the Bayesian estimation method. Results. The calculated financial multipliers confirm a significant effect of fiscal policy on GDP; expenditures on social policy and the national economy showed the greatest stimulating effect.